Effects of different pH and oxygen levels on proliferation and chondrogenic differentiation of human mesenchymal stem cells cultured in hydrogels - SINGH, SUKHDEEP (My University, 2014)
Low back pain is a very common health problem and 70-85% of the world’s population suffers from it at some point in their life. One possible cause for this pain is intervertebral disc (IVD) degeneration. Current treatments for IVD degeneration include surgical treatments which are very invasive. Thus there is a need for a strategy which is minimally invasive and for this cell therapy could be a solution. The IVD degeneration often starts in the center of the IVD, in the nucleus pulposus (NP), where chondrocyte-like cells reside. As human mesenchymal stem cells (hMSC) can undergo chondrogenic differentiation, these cells are a good candidate for the use in cell therapy to treat IVD degeneration. Transplantation of these cells together with a hydrogel into a degenerated IVD is thought to arrest the degeneration as hMSC could undergo chondrogenic differention while the hydrogel acts as a temporary matrix. The environment inside a degenerated IVD is hypoxic and acidic and thus the effects of these factors on the hMSC are important to study. The aim of this study was to evaluate the effects of different pH and oxygen levels on the proliferation and chondrogenic differentiation of human bone marrow-derived MSC cultured in the hydrogels HydroMatrix™ and PuraMatrix™. In the oxygen experiment, cells were cultured in the hydrogels for 14 days at either 10% O2 or 21% O2 (standard cell culturing condition). In the pH experiment, cells were cultured in a hydrogel for 6 days either at 10% O2 or 21% O2 and the pH levels tested were pH 7.4 (standard cell culturing condition), 7.1, 6.8 and 6.5 representing pH levels in healthy and degenerated IVDs. FACS was used to characterize the hMSC population and it could be concluded that the vast majority of the cells were in fact MSC. The results from the oxygen experiment showed gene and protein expressions of SOX9 and gene expression of collagen IIA1 in MSC cultured in HydroMatrix™ at both oxygen levels indicating chondrogenic differentiation. In addition, sulfated glycosaminoglycans were present in samples of hMSC cultured in HydroMatrix™ at 10% O2 indicating that a decreased oxygen level of 10% O2 could induce chondrogenic differentiation of hMSC. Cells were also shown to proliferate in HydroMatrix™ at both oxygen levels as cells positive for PCNA were observed in IHC studies. In the PuraMatrix™ samples, SOX9 and collagen IIA1 gene expressions were observed in some samples showing indications of chondrogenic differentiation. Deviating trends of HIF-1α gene expression were observed which suggested that 10% O2 might not be low enough to induce the HIF-1α gene. In the pH experiment, the results showed that the presence of viable hMSC decreased with decreasing pH, indicating that a decreased pH affects the survival of hMSC by resulting in a lower cell viability. However, some viable cells could be observed when cultured in HydroMatrix™ at pH 6.8 and 10% O2. This indicated that some hMSC could survive in the pH found in mildly degenerated IVDs at a decreased oxygen level of 10% O2. When comparing the results of culturing hMSC at different pH at 10% O2 with 21% O2, no clear difference in the presence of viable or dead cells could be observed however, quantification was not performed. Thus it cannot be said whether a combination of decreased pH and an oxygen level of 10% has a stronger negative effect on the survival of hMSC than a decreased pH alone.
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Bioteknologi med applikationer på växter och djur; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Agricultural Biotechnology